2018
DOI: 10.5507/fot.2017.023
|View full text |Cite
|
Sign up to set email alerts
|

Difference without distinction? Gaps in cyanobacterial systematics; when more is just too much

Abstract: Cyanobacteria are amongst the most abundant, ubiquitous, ecologically and evolutionarily significant microbes on Earth. Unique among the Bacteria in their capacity to be identified using morphology, understanding the evolutionary relationships and describing the diversity of this lineage is both important and challenging. The advent of modern sequencing technology has proven a boon to those studying cyanobacterial systematics as it has provided copious amounts of sequence data (mainly of the 16S rRNA gene sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…On the one hand, the low number of affiliations was due to the recent general low availability of genomic sequences from cyanobacteria when compared to other prokaryotes [47]. In the same time, five of the NCBI sequences used in the obtained phylogenetic tree (Figure 9) were based on metagenomic data (genetic material recovered directly from uncultured organisms from environmental samples- [48]). Despite the increased application of these data in modern studies based on the common difficulties, or even impossibility, to culture some cyanobacteria [47], their use in identification work is problematic because of the lack of morphological descriptions for most of the sequenced uncultured strains.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the low number of affiliations was due to the recent general low availability of genomic sequences from cyanobacteria when compared to other prokaryotes [47]. In the same time, five of the NCBI sequences used in the obtained phylogenetic tree (Figure 9) were based on metagenomic data (genetic material recovered directly from uncultured organisms from environmental samples- [48]). Despite the increased application of these data in modern studies based on the common difficulties, or even impossibility, to culture some cyanobacteria [47], their use in identification work is problematic because of the lack of morphological descriptions for most of the sequenced uncultured strains.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used tree-based methods (GMYC, bPTP) on the 16S rRNA dataset [96][97][98][99], and found that the results of the similarity method were almost in accord with those of tree-based analyses. Dvořa ´k et al [100] only used the PTP method, and proved that it could adequately delimit the cyanobacterial species. In the current study, the GMYC approach was more adept at recognizing species than the bPTP and ABGD approaches.…”
Section: Plos Onementioning
confidence: 99%
“…Identity in 16S rRNA should be more than 97% after Stackebrandt et al [71], or 95-96% of the whole-genome average nucleotide identity (ANI) [72]. Despite remarking the lack of a generally accepted quantitative threshold of genetic distance to describe a prokaryotic species, Willis and Woodhouse [16] showed that species delimitation in the cyanobacterial genera Raphidiopsis and Microcystis could be assessed with species boundaries occurring at ∼96% average nucleotide identity at the genomic level, together with a constrained homologous recombination capability.…”
Section: Do the Nomenclatural Entities That We Recognize As Differentmentioning
confidence: 99%
“…HGT events would be more frequent between species sharing a common particular environment and higher phylogenetic affinity, while the frequency of HGT events would be proportionally inverse with respect to the genomes genetic distance [16,60]. Therefore, the differential capability of DNA exchange through HGT may be the most important factor for species delimitation in cyanobacteria.…”
Section: Do the Nomenclatural Entities That We Recognize As Differentmentioning
confidence: 99%
See 1 more Smart Citation